Eosinophilic/T-cell Chorionic Vasculitis: Histological and Clinical Correlations. (1st April 2015) - Cheek, Bradley; Heinrich, Stephen; Ward, Kenneth; Craver, Randall
Abstract : Eosinophilic T-cell chorionic vasculitis (E/TCV) is composed of eosinophils and T-lymphocytes originating within chorionic vessels, radiating toward the intervillous space and away from the amnion in a fashion different from the fetal vascular response seen in amnionitis. Clinical significance and risk factors are not well established. We report four pregnancies (five infants, one triplet was spared) with E/TCV, gestational ranging from 23 weeks to term. All had concurrent acute chorioamnionitis, three had the typical acute fetal inflammatory response. One had placental fetal obstructive vasculopathy and an upper extremity reduction defect (radio-ulnar synostosis), the mother had pre-eclampsia. A second case involved 2 of 3 23 week previable triplets. Our third case had a metatarsus varus resistant to casting, the mother had gestational diabetes. The last case was a normal infant. We review the literature, discuss the clinical findings and present the histologic characteristics of this infrequently recognized lesion.